Identifikasi Miskonsepsi Peserta Didik SMA Menggunakan Four-Tier Diagnostic Test Berbasis Masalah Kontekstual Berbantuan Quizizz Pada Materi Gerak Lurus - Natasya Mustika Elvina Rossa; Woro Setyarsih (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to describe the quality of the questions in terms of the validity and reliability of the four-tier diagnostic test instrument as well as identifying students' misconceptions regarding rectilinear motion material using the four-tier diagnostic test. This research is research using the Ex Post Facto method with a quantitative descriptive research type. The quality of the questions is reviewed in terms of instrument validity, namely internal validity including content, construct and language, then external validity including content and construct. The results of the analysis in this study show that the internal validity for the content, construct and language domains is 91%, 90% and 91% respectively. External validity includes content with respective false positives and false negative values ​​of 9.0% and 7.33%, then the construct aspect produces a value of 0.47. The reliability of the instrument shows that rcount = 0.420. The factors that cause misconceptions experienced by students originate from within themselves, originating from humanistic thinking with a percentage of 25.98%, then from preconceptions, associative thinking, wrong intuition and wrong reasoning with percentages of 18.38%, 15.44%, 5.88% respectively, and 5.64%.